MYC-microRNA-9-metastasis connection in breast cancer - Almeida, Maria Inês (2010)
[Excerpt] Metastasis accounts for more than 90% of cancer patients’ mortality. The metastatic process involves multiple steps [1]. Initially, cancer cells from the primary tumor invade adjacent stroma. To acquire this capacity, cells undergo a process called epithelial-mesenchymal transition (EMT), in which cells in re-sponse to signals from the surrounding stroma, undergo a switch between cell phenotypes and acquire mesenchymal properties and show reduced intercel-lular adhesion, allowing cells to be-come motile. Then cells enter systemic circulation, either through the blood or lymph, and finally extravasate into the parenchyma of distant tissues, where they form micrometastasis and prolifer-ate to form secondary tumors [2]. [...]